Islamic Economic Principles for Urban Poor’s Economic Adaptation in Panjang, Bandar Lampung During Covid-19 - Hidayati, Dewi Ayu; Ariyanto, Komang; Ibrahim Musaddad, Aliyu (Universitas Islam Negeri Raden Intan Lampung, 2024)
In Indonesia, the Covid-19 pandemic, declared by the World HealthOrganization in 2019, has significantly impacted various sectors, especially theurban poor. This research examines the role of Islamic economic principles inguiding the economic adaptation strategies of the urban poor in the Panjang,Bandar Lampung, during the Covid-19 crisis. This study employs aphenomenological approach, with data collected through focus groupdiscussions, in-depth interviews, observations, and documentation. The datawere analyzed through data reduction, data presentation, and conclusiondrawing. The results show that Islamic economic principles—such as mutualsupport, equitable resource distribution, and effective debt management—played a crucial role in enabling economic adaptation. These adaptationsinclude pursuing additional income-generating activities, practicing prudentfinancial management, and seeking assistance from government programs,donors, and the private sector. In conclusion, integrating Islamic economicprinciples can enhance resilience and ensure the sustainability of livelihoodsamong the urban poor during crises.